Empowering undergraduates’ students: Digital talent development through self-directed learning - Muhammad Faiq Irfan Ismail; Livenniya Sivagumar; Nor Farah Syahira Mohd Kamal; Nurul Anisa Husna Azman (2024)
This study aims to explore how Universiti Malaysia Kelantan's undergraduate students are empowered through self-directed learning to develop their digital talents. This study has taken the FKP faculty student population of 3559 students in Pengkalan Chepa. The study uses an online questionnaire survey approach to collect data from a convenience sample of 420 city campus students. The online questionnaire is also used to gather data from users of social media and internet applications. The data were collected through the implementation of a digital tool, "Google Form." The results indicated that students in the self-directed learning group demonstrated significantly higher proficiency in digital skills compared to their counterparts in the traditional instruction group. This research offers valuable insights into the tangible benefits of employing self-directional learning strategies in digital talent development.